Theoretical and experimental studies of an oseltamivir–triazole-based thermoresponsive organogel. Issue 36 (4th July 2019) - Kumar, Sumit; Wu, Lidong; Sharma, Neha; Ayushee,; Kaushik, Kumar; Grishina, Maria; Chhikara, Bhupendra S.; Poonam,; Potemkin, Vladimir; Rathi, Brijesh
Abstract : Low-molecular weight organic gelators have been of significant interest in recent years because of their interesting properties and potential applications in sensing technology, biomedicine and drug delivery. Abstract : Low-molecular weight organic gelators have been of significant interest in recent years because of their interesting properties and potential applications in sensing technology, biomedicine and drug delivery. Herein, the synthesis, characterization and gelation properties of new oseltamivir conjugates are reported. The oseltamivir–triazole conjugate1 was synthesized via a click-reaction in a 75% yield. The key features of this conjugate include the presence of amide, flexible ester linkages and a triazole scaffold linking a hydrophobic alkyl chain. The conjugate1, possessing a long alkyl chain, showed gelation properties in various apolar organic solvents. This gelation behavior was not observed in the case of the deesterified conjugate2 ; this indicated the necessity of the alkyl chain for gelation. The gelator1 showed thermoreversible gelation properties in a range of linear alkane solvents (from n -pentane to n -dodecane). A scanning electron microscopic study suggests that the gelator1 exists as cross-linked structures, which are self-aggregated in the range of submicrometers, as supported by extensive 1 H-NMR studies. The rheological parameters supported the occurrence of a soft gelation process, and the gel formed in n -decane was found to be stiffer than that formed in n -hexane. Computational studies suggested that the gelation behavior was indeed due to micelle formation and dependent on the lipophilicity of solvents.